1996
DOI: 10.1183/09031936.96.09061269
|View full text |Cite
|
Sign up to set email alerts
|

Transfer factor (diffusing capacity) standardized for alveolar volume: validation, reference values and applications of a new linear model to replace KCO (TL/VA)

Abstract: Transfer factor (diffusing capacity) standardized for alveolar volume: validation, reference values and applications of a new linear model to replace KCO (TL/VA). D.J. Chinn, J.E. Cotes, R. Flowers, A-M. Marks, J.W. Reed. ERS Journals Ltd 1996.ABSTRACT: Transfer factor (TL) varies with alveolar volume (VA), but not in the manner implied by the carbon monoxide transfer coefficient (KCO (TL/VA)). This paper considers two other simple models (one linear and one exponential) which might standardize TL for VA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 20 publications
2
41
1
1
Order By: Relevance
“…After standardization for age, height and sex, Chinn et al [1] found a very similar relation between TL,CO and VA measured at full inflation in their population study (i.e. an inverse relationship between KCO and VA) to that found with submaximal inflation in an individual.…”
Section: Between Individualsmentioning
confidence: 68%
See 3 more Smart Citations
“…After standardization for age, height and sex, Chinn et al [1] found a very similar relation between TL,CO and VA measured at full inflation in their population study (i.e. an inverse relationship between KCO and VA) to that found with submaximal inflation in an individual.…”
Section: Between Individualsmentioning
confidence: 68%
“…The objection of Chinn et al [1] to the use of TL/VA is that "VA was the largest single contributor to the variance in TL/VA"; unfortunately, this gives the misleading impression that TL/VA is derived from TL,CO by dividing TL by VA, whereas TL/VA and VA are the two primary measurements used to obtain TL,CO. An unambiguous way to rephrase this objection would be to say that the rate constant for CO uptake varies with VA, as shown (within an individual) by Krogh [3] in 1915, and confirmed by all subsequent authors.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As noted previously, DL,CO decreases as the lung deflates as a function of both membrane and capillary configuration changes [17][18][19][20][21][22][23][24][104][105][106][107][108][109][110][111]. The relationship is complex, however, and is probably nonlinear [108,110].…”
Section: Adjustment For Lung Volumementioning
confidence: 94%